Correlation between the distance of maxillary central incisors and incisive papilla in different arch form - Mohd Zali, Nur Ateyya Natasha; Rikmasari, Rasmi; Dziab, Hasna (Universitas Padjadjaran, 2012)
In edentulous treatment, relocation of anterior teeth in the preexisting natural position is the utmost importance. It is necessary to refer to the significant anatomical landmarks, one of them is incisive papilla. To make it more efficient both functionally and biologically, the teeth were arranged in particular geometric manner known as a dental arch. The author has chosen to conducted the research among the Malay race represented by the Malay undergraduate students. The purpose of this study was to evaluate the correlation between the distance of maxillary central incisors and incisive papilla (CI-IP) in different arch form and gender. Maxillary impressions of 34 dentate individuals were taken, and the measurements were performed using a digital caliper. The results showed the CI-IP distance was ranging between 7.65 to 9.90 mm, with the average of 8.77 mm. There was no significant difference of the CI-IP distance between male and female regardless of their arch forms (p>0.05). Individuals with ovoid and tapered arch form, however, showed a significant difference of the CI-IP distance between male and female (p<0.05). Meanwhile, Individuals with square arch form showed no significant difference of the CI-IP distance between male and female (p>0.05). It can be concluded that gender factor was irrelevant towards the CI-IP distance regardless of the individual arch form. However, there was a correlation between the CI-IP distance in different arch forms in both male and female sample.